Parameter variations of 20NM GAAS junctionless-gate-all-around field-effect transistor with quantum mechanical effects - Mohamad Rasol, Muhammad Faidzal (2021)
The scaling down of nanoelectronic device dimension beyond the Moore’s Law era has introduced the use of new material and device architecture of Metal-Oxide-Semiconductor Field-Effect-Transistor (MOSFET). The use of nanomaterial and advanced device architecture allows the mitigation of the short channel effect at narrow MOSFET gate length. The purpose of this research is to study the performance of 20nm GaAs Junctionless-Gate-All-Around (JGAA) transistor incorporating the quantum mechanical effect. This device performance is then compared with conventional silicon material for comparative study. The device is designed, simulated and characterized using Technology Computer Aided Design (TCAD) from Sentaurus. The electrical parameter extracted from the current-voltage (I-V) characteristic includes the threshold voltage (Vth), drive current (Ion) and leakage current (Ioff). For JGAA MOSFET, the geometry scaling in radial direction includes the thickness of the channel radius and oxide layer, which can contribute to quantum effect. The charge distribution along the mid-region of the device is extracted to observe the carrier movement profile. Through simulation, it is proven that at shorter gate length, GaAs channel JGAA transistor exhibit better performance in terms of the on current and threshold voltage. Further evaluation shows that the classical model, the drift-diffusion model (DDM), which is the default carrier transport model, failed to incorporate the quantum effect, which is found to be non-negligible, particularly when the channel radius and oxide thickness is made less than 10nm and 14nm respectively. The inclusion of the quantum effect is based on the Density Gradient Model (DGM). It is found that the quantum effect significantly affects the drive current and leakage current by 28% for GaAs when the channel radius is scaled down less than 5nm, while minimal effect can be seen on the threshold voltage. Due to the considerable quantum effect, the carrier distribution around the channel moves further away from the semiconductor/oxide interface to the centre of the channel. This work highlight 90% increment on the on-current for GaAs JGAA MOSFET compared to silicon JGAA MOSFET and further shows the flexibility of III–V compound materials as potential materials to replace the conventional silicon. The results also indicate the necessity of considering the quantum model to generate accurate data for the projection of future nanoelectronics devices. It can be seen that this work is in agreement with other results obtained using silicon as channel for junctionless MOSFET and close with International Roadmap for Devices and Systems (IRDS) target for low power application.